On the Question on the Aggressiveness of Children and Adolescents - Gumuliauskienė, Aušrinė (Acta Paedagogica Vilnensia, 1996)
Level of aggressiveness of children and adolescents is constantly growing. The phenomena of aggressiveness therefore is interesting for both theoreticians and practitioners of education. The article discusses the understanding of aggressiveness, possible reasons for aggressive behaviour, different forms of aggressive reactions. Results of the survey of 120 pupils of 5th, 7th and 9th forms are presented. The outcomes of the research reveal the link between aggressive behaviour of parents and children’s reaction to it. One of the reasons of aggressive behaviour is the problem of interaction between teachers and pupils. Authoritarian pedagogy is named as one of the reasons for the aggressive behaviour of children.